ENRICHING THE ELEMENTARY SCHOOL STUDENTS’ VOCABULARY BY INSERTING PICTURES IN MISSING LYRICS OF CHILDREN’S SONGS - Dian Purnama Sari (LINGUA LITERA : journal of english linguistics and literature, 2020)
ABSTRACT The aim of this paper is to explain how to implement inserting pictures in missing lyrics of children’s songs technique in order to improve vocabulary. People may agree that vocabulary is important to language learning. Since the teachers do not have appropriate methods and strategies to interact with the students in the classroom, it is impossible to expect the students to be able to speak English well. Consequently, the students feel bored and even lack of their motivation in learning English. One way to make the environment in the classroom becomes interesting is by using inserting pictures in missing lyrics of children songs. This technique can be conducted as a recreational activity to avoid monotonous routines. Through inserting pictures in missing lyrics’ technique, the students will have fun and understand their lesson easily. It is expected that the students will have higher motivation because the activity could catch the interest. Furthermore, by singing a song, it can also improve students’ pronunciation.